Impact of secondary infections on dengue presentation: A cross-sectional study in a tertiary care hospital in Uttar Pradesh, India - Anju Dinkar; Jitendra Singh; Nilesh Kumar; Kailash Kumar; Santosh Kumar Singh; Arun Kumar Singh (Elsevier, 2023)
Background: Recently, a wide range variety of manifestations, including a self‑limiting to severe illness, has been increasingly reported in dengue. Few studies attract attention to severe dengue, mainly observed in secondary infection. With this background, this study aims to provide a comprehensive overview to differentiate primary from secondary dengue using serology (IgG) and the possible association of severity of illness in secondary dengue. Methods: Present retrospective cross-sectional study was conducted at a North Indian tertiary care center from September 2021 to January 2022. Clinical data of confirmed dengue patients from the medicine department were collected and assigned as primary and secondary dengue. Results: Of the 220 dengue patients, 22 (10 %) had secondary dengue infection. Hemorrhagic manifestations were reported in 58/220 (26.4 %) cases while 7/22 (31.8 %) in secondary dengue. Prevalent hemorrhagic manifestations in secondary dengue include purpura (27.3 %), vaginal bleeding (4.5 %), melaena (9.1 %), and epistaxis (4.5 %). In addition, 42 (19.1 %) patients had pancytopenia, and 8 (36.6 %) cases were of secondary dengue. Hepatic dysfunction was noted in 164 (74.5 %) cases. Notably, all secondary dengue cases (22;100 %) had hepatic dysfunction and severe in 9 (40.9 %) cases. In addition, in secondary dengue patients, evidence of plasma leakages such as hypoproteinemia 7 (31.8 %) and ascites (35 %) were statistically more frequent. Overall, two deaths (0.9 %) were reported, and were one in each group. Conclusions: Many parameters, including hemorrhagic manifestation (melaena), hematological characteristic (pancytopenia), evidence of plasma leakage (hypoproteinemia and ascites), gastrointestinal (GB wall thickening and hepatic dysfunction) and reduction in mean hemoglobin and platelet count were found to be statistically significant in secondary dengue infection. Additionally, early classification of secondary dengue may help to anticipate its severity and allow for early strategic intervention/management to lower morbidity and mortality.